Analiza problema jaza in identitete pri filozofu Davidu Humu - Šumiga, Dražen (Monitor ISH, 2008)
In this article I address the question of the self in the works of David Hume. My aim is to show that the notion of the self is a mistake, because everything is subject to the 'Heraclitean' flow of coming into being and passing away. According to Hume, we cannot construct a clear and coherent idea of the self on the basis of our impressions because they are changeable. I also present the Humean bundle theory, which understands the self as a bundle of different perceptions, constantly changing and thus precluding any adequate idea of the self. In Hume's view, it is therefore absurd to postulatean unknowable principle, such as the soul or mind.
Keywords: Hume, David, 1711-1776; identiteta; subjekt; jaz; zavest; epistemologija; epistemology